Overexpression of Ephrin A3 Receptor in Canine Prostatic Carcinoma. Issue 2 (February 2016) - Hood, G.; Laufer-Amorim, R.; Fonseca-Alves, C.E.; Palmieri, C.
Summary: Ephrin A3 (EphA3), a member of the ephrin receptor tyrosine kinase family, is involved in a variety of functions in normal cells, especially during embryonic development, and alterations in its expression profile have been observed in several human cancers. However, there are no reports of the expression of EphA3 in normal, hyperplastic or neoplastic canine prostate tissue or in other types of canine tumours. Six normal, 15 hyperplastic and 21 neoplastic canine prostates were examined immunohistochemically with a polyclonal antibody specific for human EphA3. The percentage of positive cells in all prostatic carcinomas was increased, with a mean of 89.28 ± 5.18% compared with normal (9.17 ± 6.72%) and hyperplastic prostates (20.00 ± 8.28%). EphA3 expression was not correlated with the histological subtypes of prostate cancer or with the Gleason score. The increase in EphA3 expression in canine prostatic carcinomas suggests the involvement of this receptor in prostatic carcinogenesis and its potential use as a target for new therapeutic strategies.